PERSAINGAN USAHA - Moira Shafeeya Sumadibrata; Najwa Haniyah Nasution; Prastiwi Pramudya Putri; Samuel Alberto Hutahayan; Sulastri, Sulastri (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Competition in business is an important aspect of maintaining a healthy and competitive business climate. Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition in Indonesia aims to prevent harmful business practices such as monopolies and cartels. However, despite the existence of this regulation, its implementation still faces challenges, particularly in terms of law enforcement and the understanding of business actors. This study aims to analyze the implementation of competition law in Indonesia, focusing on the role of the Indonesian Competition Commission (KPPU) in enforcing this law. The research uses a qualitative approach with literature studies, legal document analysis, and interviews with legal practitioners. The findings show that although significant efforts have been made to oversee competition, there are still shortcomings in law enforcement and coordination among related institutions. This study recommends strengthening the capacity of the KPPU and law enforcement officers, as well as the need for more intensive education for business actors to improve compliance with regulations on healthy business competition.